Acute Effect of L-Citrulline Supplementation on Resistance Exercise Performance and Muscle Oxygenation in Recreationally Resistance Trained Men and Women - Adam M. Gonzalez; Yang Yang; Gerald T. Mangine; Anthony G. Pinzone; Jamie J. Ghigiarelli; Katie M. Sell (Journal of Functional Morphology and Kinesiology, 2023)
L-citrulline serves as a nitric oxide precursor with the potential to increase blood flow and improve resistance exercise performance, yet more research is needed to examine its ergogenic potential. To examine the effect of L-citrulline supplementation on resistance exercise performance, muscle oxygenation, and the subjective perception of effort, energy, focus, fatigue, and muscle pump, eighteen resistance-trained men (n = 11) and women (n = 7) (21.4 ± 1.8 years; 172.3 ± 7.5 cm; 76.9 ± 10.8 kg) were randomly assigned for supplementation with 8 g of L-citrulline (CIT) or a placebo (PL) in a cross-over fashion one hour prior to testing. Participants completed an isometric mid-thigh pull test (IMTP), a ballistic bench press protocol [two sets of two repetitions at 75% 1-repetition maximum (1 RM) with maximum ballistic intent], and a strength-endurance bench press protocol [five repetition-maximum sets at 75% 1RM]. Barbell velocity and power were measured via a linear position transducer during the ballistic protocol, while the repetitions completed, volume load and muscle oxygenation were quantified during the strength-endurance protocol. Subjective measures were assessed at the baseline and immediately pre- and post-exercise. Repeated measures of the analysis of variance and Bayesian equivalents revealed no significant interactions, providing evidence favoring the null hypothesis (BF10 < 1) for IMTP (PL 497.5 ± 133.6 vs. CIT 492.5 ± 129.4 N), barbell velocity, and power, and repetitions completed (PL 36.7 ± 7.2 vs. CIT 36.9 ± 8.1 repetitions). There were also no significant interactions for muscle oxygenation parameters or subjective measures except perceived fatigue. Women reported greater fatigue across all time points compared to men (~1.88 au, p = 0.045, BF10 = 0.2). The results indicate that a single 8 g dose of L-citrulline did not enhance isometric force production, muscle endurance, or muscle oxygenation parameters during the protocol implemented in this study.